2010
DOI: 10.1021/ml900003t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Sansalvamide A-Amide: An Allosteric Modulator of Hsp90

Abstract: Herein we show that San A-amide, a structurally unique molecule, influences a subset of cancer-related pathways involving Hsp90. We show that San A-amide specifically binds to the N-middle domain of Hsp90 allosterically disrupts the binding of proteins thought to interact with the Hsp90 C-terminal domain, while having no effect on an N-terminal domain client protein. This unique mechanism suggests that San A-amide is a potential tool for studying C-terminal binding proteins of Hsp90 as well as a promising lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
105
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 37 publications
(90 reference statements)
5
105
0
Order By: Relevance
“…Investigations done by McAlpine and co-workers utilizing the peptide analog of San A (SM1, Fig. 1) showed that this San A derivative targeted heat shock protein 90 (Hsp90) [22]. Hsp90 is a major molecular chaperone that is involved in the progression and survival of cancer cells.…”
Section: Sansalvamide Amentioning
confidence: 99%
“…Investigations done by McAlpine and co-workers utilizing the peptide analog of San A (SM1, Fig. 1) showed that this San A derivative targeted heat shock protein 90 (Hsp90) [22]. Hsp90 is a major molecular chaperone that is involved in the progression and survival of cancer cells.…”
Section: Sansalvamide Amentioning
confidence: 99%
“…This class of macrocyclic inhibitors allosterically modulate the C-terminus of Hsp90, and include the structures SM122 and SM145. [23][24][25][26][27][28][29] 2.1.2 Heat Shock Protein 90 (Hsp90) as an Oncogenic Target…”
Section: Macrocycles As Anticancer Agentsmentioning
confidence: 99%
“…45 Homodimerisation is the active conformation of Hsp90, which has led to the C-terminal dimerisation domain (with its nucleotide binding site and MEEVD co-chaperone binding region) becoming the focus of several Hsp90 inhibitors: Class IV (SM122 and 145), which show excellent Hsp90 inhibitory activity. [23][24][25][26][27]29,46 All four classes appear to modulate the allosteric cross talk between the N-and C-termini of Hsp90. However, each macrocyclic class of compounds impacts the clients and co-chaperone binding events uniquely.…”
Section: Macrocycles As Anticancer Agentsmentioning
confidence: 99%
“…Complexes between Hsp90 and its co-chaperones are enriched in cancer cells [40], suggesting that the cancer-specific roles of Hsp90 may be linked to cooperation with these factors [41]. Indeed, sansalvamide A [42,43] and gedunin [34] are inhibitors of co-chaperone binding, and they are selectively toxic to cancer cells.…”
mentioning
confidence: 99%